Molecular dynamics of cis-1-(2-hydroxy-5- methylphenyl)ethanone oxime and N-(2-hydroxy-4-methylphenyl)acetamide in solution studied by NMR spectroscopy - Mamedov, Ibrahim Garib (Magnetic resonance in chemistry : MRC, 2010)
2010 John Wiley & Sons, Ltd.